2008
DOI: 10.1021/jp8065376
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide and Sulfide Hollow Spheres: Layer-By-Layer Synthesis and Their Application in Lithium-Ion Battery

Abstract: A novel layer-by-layer approach has been developed to synthesize polycrystalline SnO(2) hollow spheres with tunable shell thickness and size using SiO(2) spheres as a template. The surface of the SiO(2) spheres has been first modified by the polyelectrolyte, and subsequently, the compact SnO(2) layer has deposited on the surface of the SiO(2) spheres through a redox reaction because of the electrostatic attraction between the charged species. After HF etching treatment, the uniform SnO(2) hollow spheres have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 48 publications
(27 reference statements)
0
56
0
Order By: Relevance
“…Xue et al reported the synthesis of hollow doughnut-shaped and spherical CuO structures via thermal oxidation of the corresponding CuS and Cu 2 S precursors, respectively [9]. Yang's group reported layer-by-layer synthesis of polycrystalline SnO 2 hollow spheres using SiO 2 spheres as a template [10]. Xue et al studied the synthesis of hollow ZnO micro- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al reported the synthesis of hollow doughnut-shaped and spherical CuO structures via thermal oxidation of the corresponding CuS and Cu 2 S precursors, respectively [9]. Yang's group reported layer-by-layer synthesis of polycrystalline SnO 2 hollow spheres using SiO 2 spheres as a template [10]. Xue et al studied the synthesis of hollow ZnO micro- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…For the formation of hollow nanoparticles, PS nanoparticles as seen with templating hollow MSNs, are also used in conjunction with LbL to produce hollow nanoparticles of titania, silica, or laponite (synthetic clay [Na 0.7 (Si 8 Mg 5.5 Li 0.3 )O 20 (OH) 4 ]) with PDDA/PAH/PSS polyelectrolytes used as the alternating layers [343]. Silica nanoparticles also serve a similar role to PS and can be used with polyelectrolyte/metal oxide LbL techniques [344].…”
Section: Layer-by-layer Depositionmentioning
confidence: 99%
“…Another effective way to improve the stability of SnO 2 based anode materials is to design nanostructured SnO 2 with unique morphologies, which can provide higher electrode/electrolyte contact area, shorter diffusion length of Li + , and better withstanding of the huge volume change, thus leading to improved lithium storage properties [28][29][30]. In the past decade, various nanostructured SnO 2 , including nanorods [31], nanowires [7,29,[32][33][34], nanotubes [35][36][37][38][39][40][41], nanosheets [30,[42][43][44], and hollow nanospheres [3,[45][46][47][48][49][50][51], have been successfully synthesized and widely studied as anode materials, thus obtained improved electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%